A Rare Case of Nonsyndromic Multiple Cystic Pancreatic Neuroendocrine Tumors Diagnosed by Endoscopic Ultrasound-Guided Fine-Needle Aspiration. (21st September 2018) - Wang, Tiannan; Raza, Anwar; Choo, Evelyn
Abstract: In comparison with solid pancreatic neuroendocrine tumors (PanNETs), cystic PanNETs (c-PanNETs) are uncommon and represent about 17% of PanNETs. They are typically unilocular, solitary, and discovered incidentally in the tail of pancreas. Multiple c-PanNETs are especially rare and have been reported to be associated with genetic disorder syndromes, such as multiple endocrine neoplasia I (MEN I) and von Hippel Lindau syndrome (VHL). Endoscopic ultrasound-guided fine-needle aspiration (EUSFNA) is a minimally invasive modality for detecting and diagnosing gastroenteropancreatic neoplasms and is particularly sensitive in the setting of recognizing pancreatic adenocarcinoma. However, the accuracy and sensitivity are reportedly lower in the detection of c-PanNETs. Herein, we present a diagnostically challenging c-PanNET case by EUSFNA in a 64-year-old male with no known syndromic disease who presented with multiple cystic lesions in the pancreatic head, uncinate process, and tail, measuring from 2.0 to 5.2 cm. Papanicolaou-stained ThinPrep slides of the two largest cystic lesions from the uncinate process and tail identified multiple well-preserved small clusters of tumor cells showing round with slightly overlapping nuclei, coarse stippled chromatin, and eosinophilic cytoplasm. In addition, a significant number of the cells demonstrated clear to foamy cytoplasm in one of the cysts. Mitotic figures were not identified. Immunostains performed on both cysts showed immunoreactivity for the neuroendocrine markers synaptophysin, chromogranin, and CD56, confirming the presence of multiple c-PanNETs. An inhibin immunostain was performed on the cyst, which showed a population of foamy cells to evaluate for the possibility of the clear cell variant of c-PanNET, which has been associated with von Hippel Lindau syndrome. The inhibin stain was negative, but a CD68 immunostain was positive due to the presence of macrophages, consistent with the cystic nature of these sporadic pancreatic lesions.